Barrier and mechanical properties of carbon steel coated with SiOx/SiOxCyHz gradual films prepared by PECVD - Rangel, Rita C.C. [UNESP]; Cruz, Nilson C. [UNESP]; Milella, Antonella; Fracassi, Francesco; Rangel, Elidiane C. [UNESP] (Elsevier, 2019)
Carbon steel is the most commonly used material for sheets, plates, bars and tubes in mechanical metallurgy and construction industry. However, the susceptibility of carbon steel to oxidation under real conditions of use turns preventive and corrective repairs mandatory. Many published studies show that plasma deposited silica and organosilicon layers can be used as corrosion barriers, being the first one more efficient due to its higher chemical density and inertness. However, the performance of SiOx layers may be affected by mechanical stress, and especially by defects generated in the deposition process or by the substrate finishing. To associate the good corrosion resistance of the silicon oxide films to the flexibility of organosilicon ones, some authors created multilayered systems, intercalating organosilicon and silica layers. However, the adhesion between the organosilicon and inorganic layers in these multilayered systems is still a problem, since there is a well-defined interface between them and both layers are just slightly interconnected. In this sense, the purpose of the present work is to create, from plasma polymerization of hexamethyldisiloxane, an organosilicon-silica gradual system and to investigate its barrier and mechanical properties. SiOx/SiOxCyHz gradual films were deposited by low pressure radiofrequency (13.56 MHz) plasmas using HMDSO, Ar and O2 mixtures. The change of an organosilicon to inorganic coating or vice versa was made only by adjusting the plasma conditions without interrupting the process. The influence of the carbon steel native oxide pre-deposition treatment in O2 plasma was also evaluated. Electrochemical Impedance Spectroscopy, EIS was used to evaluate the corrosion resistance provided by the gradual system to the carbon steel. Infrared spectroscopy, FTIR, was applied to analyze the chemical composition and molecular structure. The thickness of the films was measured by profilometry. Surface wettability was assessed from contact angle measurements using an automated goniometer. The morphology of the samples was inspected by secondary electrons micrographs acquired using a scanning electron microscope while the mechanical properties of the systems were examined by nanoindentation. The oxidation treatment performed on the substrate surface prior to deposition improve the corrosion resistance of the samples. The total corrosion resistance increases six orders of magnitude when carbon steel was coated with a quaternary gradual coating of only 2 μm.
Keywords: Corrosion resistance; HMDSO; Mechanical properties; Plasma deposition; SiOx/SiOxCyHz gradual layers